PENYULUHAN TENTANG PENERAPAN NILAI-NILAI PLURALISME DI DESA HAURKOLOT, INDRAMAYU - Rahim, Abdur; Amalia, Iqlimah; Zianilah, Difani; Fadhillah, Rafif Ahmad; Fajrin, Jihan Aulia; Juwita, Almi Maliana; Islami, Bilat Nur; Difa, Maulana Dzidan Al (LPPM Universitas Bina Bangsa, 2024)
Pluralism is an important concept in understanding diversity and the way people live side by side in harmony. Aspects of pluralism include religious diversity, recognition and acceptance of various religions and beliefs that exist in society. If we want to understand and be able to apply the values of pluralism in everyday life, we must first understand the basic values of pluralism itself. The aim of implementing this community service is to provide outreach about the application of pluralist values in Haurkolot village, Indramayu. This Community Service Activity aims to provide education regarding the application of pluralist values in Haurkolot village, Indramayu Regency. The result of this activity is to know the values of pluralism, including: tolerance, equality, dialogue, inclusiveness, and recognition of identity. These values of pluralism are very important in building a peaceful, just and harmonious society. By implementing tolerance, equality, dialogue, inclusivity, and identity recognition, we can create an environment where differences are seen as strengths, not as sources of conflict. Among the conflicts that arise in society are related to religious intolerance, such as At-Tadayyun Al- Manqus, which is a phenomenon that must be watched out for in religious life. It is important for each individual to try to understand and practice religion as a whole, so as not to be trapped in incomplete religious practices. So the benefits of pluralism in social life include increasing creativity and innovation, strengthening social cohesion, learning and self-development, reducing conflict, increasing quality of life, empowering minority groups, and economic development. Collective efforts from individuals, com munities and governments are needed to realize true pluralism and gain full benefits from it